Improved intestinal lymphatic drug targeting via phospholipid complex-loaded nanolipospheres of rosuvastatin calcium. Issue 10 (20th January 2016) - Beg, Sarwar; Raza, Kaisar; Kumar, Rajendra; Chadha, Renu; Katare, O. P.; Singh, Bhupinder
Abstract : The present work describes the systematic development and characterization of nanolipospheres (NLPs) loaded with phospholipid complex of rosuvastatin for enhanced oral drug absorption trough lymphatic pathways. Abstract : The present work describes the systematic development and characterization of nanolipospheres (NLPs) loaded with phospholipid complex of rosuvastatin for enhanced oral drug absorption trough lymphatic pathways. The construction of Job's plot revealed 3 : 1 as the apt stoichiometric ratio for formation of complex between the drug and phospholipid. The complex was characterized by FT-IR, DSC, PXRD, H 1 -NMR, SEM and molecular docking studies. Evaluation of the complex for aqueous solubility and dissolution studies revealed 4.4- and 3.8-fold improvement in the solubilized fraction and release rate of the drug as compared to the physical mixture and pure drug. Further, the complex-loaded NLPs were prepared by phase inversion method and systematically optimized using Box–Behnken design, selecting the amounts of Compritol 888 (X1 ) and Solutol HS15 (X2 ) as the product parameters, and stirring speed (X3 ) as the process parameter. The prepared formulations were evaluated for particle size, zeta potential, encapsulation efficiency and in vitro drug release. Ex vivo permeation and in situ intestinal perfusion studies revealed 4.2 to 6.5-fold improvement in the permeability and absorption of the drug from NLPs vis-à-vis the complex, physical mixture and pure drug. In vivo pharmacokinetic studies corroborated significant improvement in C max (4.7-fold) and AUC (5.3-fold) by the complex-loaded NLPs in comparison to the physical mixture and pure drug. The lymphatic distribution studies construed 4.8-fold augmentation in the uptake of drug from NLPs over the erstwhile formulations. Pharmacodynamic studies also revealed superior efficacy of the NLPs in reducing the serum cholesterol, LDL, triglycerides, and increasing the HDL over the pure drug. Overall, the studies indicated enhanced biopharmaceutical performance of the NLPs loaded with phospholipid complex of rosuvastatin calcium.